INDUCTION OF APOPTOSIS BY XANTHONES FROM GARCINIA MANGOSTANA IN HUMAN BREAST AND LARYNGEAL CARCINOMA CELL LINES - S. CHITRA; M.V. KRITHIKA; S. PAVITHRA (International Journal of Pharma and Bio Sciences, 2010)
The present study is an attempt to evaluate the standardization of crude mangosteen and γ – mangostin from Garcinia mangostana on MCF-7 (breast cancer cell line) and Hep2 (laryngeal cancer cell line). The study includes cell doubling time, ED50 analysis (growth inhibition), cell proliferation assay and assessment of cell cytotoxicity by dye exclusion assay. The result of the study showed that the cell doubling time was found to be 72 hours for MCF -7 cells and 48 hours for Hep2 cells. Growth inhibition assay for MCF-7 and Hep2 showed 2.5 and 5.25µg (crude mangosteen) and 0.85 and 1.75µg (γ – mangostin) respectively. The mitochondrial survival and cell cytotoxicity was significantly less when compared to control groups.